PROBLEMATIKA GURU DALAM PEMBELAJARAN TEMATIK KELAS IV A DI SEKOLAH DASAR NEGERI 1 MENTAWA TAHUN PELAJARAN 2021/2022 - Yudi Hermawan; Hifza; Topik (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2022)
The purpose of This research aims to reveal about: 1) Teacher problems in planning thematic learning for class IV A at SDN 1 Mentawa for the 2021/2022 academic year; 2) Teacher problems in implementing thematic learning for class IV A at SDN 1 Mentawa for the 2021/2022 academic year; and3) Teacher problems in assessing thematic learning for class IV A at SDN 1 Mentawa for the 2021/2022 academic year. his study uses a qualitative approach and a type of phenomenological research. Data collection techniques using interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions and verification. The results showed that: Teacher problems in planning thematic learning for class IV A at SDN 1 Mentawa for the 2021/2022 academic year, namely: a) obstacles in preparing lesson plans, b) Problems in developing syllabus, c) Obstacles in determining creative learning media, d) Problems in determining learning methods, e) The lack of learning material. Problems with teachers in implementing thematic learning for class IV A at SDN 1 Mentawa for the 2021/2022 academic year, namely: a) difficulties in connecting learning activities with students' real lives, b) difficulties in managing classes, c) problems in applying learning methods. Teacher problems in assessing class IV A thematic learning at SDN 1 Mentawa for the 2021/2022 Academic Year, namely a) Difficulties in carrying out daily assessments, b) Difficulties in reporting final grades.